G322 The association between trajectories of bedwetting and daytime wetting in childhood and incontinence and lower urinary tract symptoms in adolescence. (27th April 2016) - Joinson, C; Grzeda, M; von Gontard, A; Wright, A; Heron, J
Abstract : Aims: This is the first prospective cohort study to examine the association between developmental trajectories of childhood incontinence and adolescent incontinence and lower urinary tract symptoms (LUTS). Methods: We used longitudinal latent class analysis to identify developmental trajectories of bladder control using maternal reports of their child's incontinence from 4–9 years in 8, 751 participants from the Avon Longitudinal Study of Parents and Children. We then used logistic regression to examine the association between the trajectories and self-reported bedwetting, daytime wetting, nocturia, urgency, high voiding frequency and voiding postponement at 14 years. Results: We identified five trajectories: (i) Normative development of daytime and nighttime bladder control (63.1% of the sample), (ii) Delayed attainment of bladder control (8.6%), (iii) Bedwetting alone (no daytime wetting) (15.6%), (iv) Daytime wetting alone (no bedwetting) (5.8%), (v) Persistent wetting (bedwetting with daytime wetting to age 9) (7.0%). There were increased odds of bedwetting at 14 years among those with persistent wetting in childhood (odds ratio=23.5, 95% confidence interval=15.1–36.4) and bedwetting alone (3.69 [2.21–6.17]) (reference category: normative development). Odds of daytime wetting at 14 years were increased among those with daytime wetting alone (odds ratio=10.1 [6.70–15.3]) and persistent wetting (6.98 [4.50–10.8]). There were increased odds of nocturia (2.39 [1.79–3.20]) and urgency (2.10 [1.44–3.07]) in adolescence among those with persistent wetting in childhood and increased odds of voiding postponement (1.94 [1.48–2.54]) in those with daytime wetting alone. Conclusions: We find evidence that trajectories of incontinence in childhood are differentially associated with adolescent incontinence. Bedwetting in adolescence was more likely in those who experienced persistent wetting in childhood compared with bedwetting alone. Daytime wetting in adolescence was associated with childhood daytime wetting and persistent wetting. LUTS were more common among adolescents who experienced childhood incontinence than those who had normal development of continence. The awareness of particular patterns of incontinence is important in clinical practice because children exhibiting incontinence trajectories associated with poor outcomes in adolescence should be prioritised for investigations and treatment.